Expression and Subcellular Localization of Retinoic Acid Receptor-α (RARα) in Healthy and Varicocele Human Spermatozoa. Issue 5 (May 2015) - Perrotta, Ida; Perri, Mariarita; Santoro, Marta; Panza, Salvatore; Caroleo, Maria C.; Guido, Carmela; Mete, Annamaria; Cione, Erika; Aquila, Saveria
<x xml:space="preserve">Abstract</x> Varicocele, an abnormal tortuosity and dilation of veins of the pampiniform plexus, is the most common identifiable and correctable cause of male infertility. It is now becoming apparent that signaling through vitamin A metabolites, such as all-trans retinoic acid (ATRA), is indispensable for spermatogenesis and disruption of retinoic acid receptor-α (RARα) function may result in male sterility and aberrant spermatogenesis. Herein, we investigated by Western blot and immunogold electron microscopy the expression profiles and subcellular localization of RARα in healthy and varicocele human sperm; in addition, we analyzed the effects of ATRA on cholesterol efflux and sperm survival utilizing enzymatic colorimetric CHOD-PAP method and Eosin Y technique, respectively. In varicocele samples, a strong reduction of RARα expression was observed. Immunogold labeling evidenced cellular location of RARα also confirming its reduced expression in "varicocele" samples. Sperm responsiveness to ATRA treatment was reduced in varicocele sperm. Our study showed that RARα is expressed in human sperm probably with a dual role in promoting both cholesterol efflux and survival. RARα might be involved in the pathogenesis of varicocele as its expression is reduced in pathologic samples. Thus, ATRA administration in procedures for artificial insemination or dietary vitamin A supplementation might represent a promising therapeutic approach for the management of male infertility.